2019
DOI: 10.1111/ped.14025
|View full text |Cite
|
Sign up to set email alerts
|

Complications of herpes zoster in children

Abstract: BackgroundHerpes zoster (HZ) may cause complications; however, information regarding complications of HZ in children is relatively sparse. We reviewed cases of HZ in children retrospectively and investigated the risk factors contributing to the development of complications.MethodsA retrospective observational study was conducted at a tertiary care children’s hospital in Japan. Children receiving a diagnosis of HZ between January 2010 and October 2016 were identified from electronic medical records. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
0
22
0
2
Order By: Relevance
“…Indeed, PRF at ICN can also relieve PHN. When the body’s immunity reduces, the latent virus always replicates along the sensory nerve reaching the corresponding skin area, which results in peripheral nerve necrosis, inflammation, and demyelination [ 27 ]. Peripheral nerve sensitization plays a particularly important role in neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PRF at ICN can also relieve PHN. When the body’s immunity reduces, the latent virus always replicates along the sensory nerve reaching the corresponding skin area, which results in peripheral nerve necrosis, inflammation, and demyelination [ 27 ]. Peripheral nerve sensitization plays a particularly important role in neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…PHN is regarded the most common complication in adults and an important complication of HZ due to its impact on quality of life. However, the incidence in children has been low, as in our study [25,26]. In this analysis, the involved nerve roots varied from cranial to lumbar, and PHN cases predominantly involved older aged patients.…”
Section: Discussionmentioning
confidence: 48%
“…Most patients did not have any underlying diseases. Previous studies on children have also demonstrated that complicated cases tend to develop in immunocompetent children [25,26], and German data showed that immunocompetent children accounted for most hospitalizations and complications (25). Therefore, awareness regarding HZ complications and preventive measures is not only important in older people but also in immunocompetent and younger populations.…”
Section: Discussionmentioning
confidence: 96%
“…Pediatric HZ has a good prognosis. The most common complication among immunocompetent children is a bacterial skin infection, while postherpetic neuralgia, the most common complication in adults, is less frequent in children [20].…”
Section: Discussionmentioning
confidence: 99%